KINERJA PELAYANAN PEMBINAAN KEPADA WARGA BINAAN PEMASYARAKATAN DI RUMAH TAHANAN NEGARA KELAS I SURAKARTA - Eka Dewi Sutrisno (Master of Public Administration, Universitas Slamet Riyadi, 2021)
The study purpose was described and analyzed the performance of coaching services to the Prisoners in Rumah Tahanan Kelas I Surakarta. The research type is qualitative descriptive. The data used primary and secondary data. The data collecting techniques were used interviews, observation, and documentation. The data analysis technique was used the Miles and Huberman’s interactive model. Data validity testing was used triangulation techniques. Based on the research results can be concluded that 1) 1) Productivity of Rumah Tahanan Kelas I Surakarta in the coacing service is good; 2) The service quality of Rumah Tahanan Kelas I Surakarta is quite good; 3) Responsiveness of Rumah Tahanan Kelas I Surakarta is good; 4) Responsibility of Rumah Tahanan Kelas I Surakarta is good; and 5) Accountability of Rumah Tahanan Kelas I Surakarta is good.